2002
DOI: 10.1037/0021-9010.87.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Business-unit-level relationship between employee satisfaction, employee engagement, and business outcomes: A meta-analysis.

Abstract: Based on 7,939 business units in 36 companies, this study used meta-analysis to examine the relationship at the business-unit level between employee satisfaction-engagement and the business-unit outcomes of customer satisfaction, productivity, profit, employee turnover, and accidents. Generalizable relationships large enough to have substantial practical value were found between unit-level employee satisfaction-engagement and these business-unit outcomes. One implication is that changes in management practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

103
2,834
10
138

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,253 publications
(3,085 citation statements)
references
References 31 publications
103
2,834
10
138
Order By: Relevance
“…However, the relationship between unit capacity as an indicator of staffing adequacy and nurse safety outcomes has not been previously described. Similarly, while studies have not examined the relationship between work engagement and nurse safety outcomes, Harter, Schmidt, and Hayes (2002) found that higher work engagement among employees in industrial organizations was associated with fewer work days lost due to injury. This finding lends support to the argument that employee safety depends not only on compliance with safety rules but also voluntary participation in safe work practices, participation that is strongly influenced by involvement in and commitment to the work.…”
Section: Organizational Structurementioning
confidence: 99%
“…However, the relationship between unit capacity as an indicator of staffing adequacy and nurse safety outcomes has not been previously described. Similarly, while studies have not examined the relationship between work engagement and nurse safety outcomes, Harter, Schmidt, and Hayes (2002) found that higher work engagement among employees in industrial organizations was associated with fewer work days lost due to injury. This finding lends support to the argument that employee safety depends not only on compliance with safety rules but also voluntary participation in safe work practices, participation that is strongly influenced by involvement in and commitment to the work.…”
Section: Organizational Structurementioning
confidence: 99%
“…As indicated earlier, there is a general belief that there is a connection between employee engagement and business results 33 . However, engagement is an individual-level construct and if it does lead to business results, it must first impact individual-level outcomes.…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…Job satisfaction, a widely researched construct, is defined as a pleasurable or positive emotional state resulting from the appraisal of one's job or job experiences 21 22 begin their discussion of engagement by using the term engagement-satisfaction, but drop the satisfaction from the term early in their article. It has been found that while the relationship between job satisfaction and performance is weak at the individual level, but is stronger at the aggregate level (Ostroff, 1992) 23 .…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shuck (2011) identified four emerging themes generally used to define approaches to understanding EE. (1) The needsatisfying approach (Kahn, 1990); (2) the burnout-antithesis approach (Maslach et al, 2001); (3) the satisfaction-engagement approach (Harter, Schmidt, & Hayes, 2002); and (4) the multidimensional approach (Saks, 2006).…”
Section: Employee Engagementmentioning
confidence: 99%